2007
DOI: 10.1080/09540120601114485
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers as a cornerstone for integrating HIV and primary healthcare

Abstract: Haiti is the poorest and most heavily HIV-burdened country in the Western hemisphere, with even less health infrastructure than many countries of sub-Saharan Africa. Since the early 1980s the HIV epidemic has affected the poorest communities in Haiti, who lack access to even basic healthcare. Large-scale HIV treatment requires that basic healthcare services be built and scaled up simultaneously with HIV-prevention and -care programmes. Such improvement in access to general healthcare will require substantial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 8 publications
4
102
0
1
Order By: Relevance
“…Some innovative ways to strengthen the health workforce would be: (1) to encourage retention and motivation of current workers through better, safer work environments; (2) to build leadership capacity in the workforce, potentially by mobilizing the Zimbabwean health diaspora to engage in training and skill-building among the current workforce [3]; and (3) to place a greater reliance on mid-level and non-specialist providers [32] and on community members including community health workers (CHWs) [3336] and traditional healers [3740]. …”
Section: Strengthen the Health Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Some innovative ways to strengthen the health workforce would be: (1) to encourage retention and motivation of current workers through better, safer work environments; (2) to build leadership capacity in the workforce, potentially by mobilizing the Zimbabwean health diaspora to engage in training and skill-building among the current workforce [3]; and (3) to place a greater reliance on mid-level and non-specialist providers [32] and on community members including community health workers (CHWs) [3336] and traditional healers [3740]. …”
Section: Strengthen the Health Workforcementioning
confidence: 99%
“…This will mean hiring Zimbabweans, building capacity, and listening carefully to local priorities. Community health models, often using community health workers, have been successful in many areas of global health including HIV/AIDS, child health, malaria, and tuberculosis [33,35,36]. Although a village health worker program was installed in the 1980s via the Health Transition Fund, this effort was limited by a lack of true community participation and a bureaucratic top-down approach where decisions were still made by the Ministry of Health [2].…”
Section: Prioritize Communitiesmentioning
confidence: 99%
“…However, the criteria for defining suitable knowledge and the instruments used for measuring knowledge level have varied between studies and research findings have been contradictory. Some studies have suggested that health workers have a "sufficient level" of knowledge (7,8) but others have reported deficient knowledge in several areas like prevention, transmission, diagnosis and treatment (9,10). A few studies in Chile have analyzed secondary and tertiary level health workers' HIV knowledge and found their knowledge to be deficient regarding transmission (11).…”
Section: Introductionmentioning
confidence: 99%
“…The voluntary work that people, often women, do in community organisations takes them away from their own homes and draws heavily on personal resources. While the Haiti study shows that community health workers improve the outreach and effectiveness of health services, not S86 R. Loewenson all services finance this contribution as the Haiti services do (Mukherjee & Eustache, 2007). The studies also signal that the withdrawal or weakening of the state has left communities disadvantaged and, conversely, that strong public and community institutions are critical for an equitable response.…”
Section: Network Of Support In Responses To Vulnerabilitymentioning
confidence: 97%
“…There are some contrasting positive examples as well: the international resource support to the provision of integrated primary healthcare in Haiti in ways that seek to reinforce the public sector infrastructure, linking communities to services through community health workers, provides one example of such vertical connections (Mukherjee & Eustache, 2007). The support by KENWA to provide treatment to women in the Nairobi informal settlements is another.…”
Section: Network Of Support In Responses To Vulnerabilitymentioning
confidence: 99%